Analisis Faktor-Faktor Yang Mempengaruhi Kredit Bermasalah Di Bank BRI Unit Gumilir Cilacap - Zamroni, Zamroni (JURNAL EKONOMI, 2014)
The purpose of this study to Analyst Factors that Effect Problem Loan in Bank Rakyat Indonesia Unit Gumilir Cilacap.. Innfluence Credit (5C) partially composed of Character (X1), Capacity (X2), Capital (X3), Collateral (X4), Condition of Economy (X5) against Smoothness Payments (Y) Installment Customers Bank Rakyat Indonesia Unit Cilacap, proving the influence Prerequisites Credits (Character, Capacity, Capital, Collateral, Conditions of Economy) simultaneously on the smoothness of Payments Installment of Customer in Bank BRI Unit Cilacap and prove variable (Character, Capacity, Capital, Collateral, Conditions of Economy) in which the most significant effect on the Payment Smoothness Installment of Customer in Bank BRI Unit Gumilir Cilacap..The study population is the Customer in Bank BRI Unit Gumilir Cilacap which amounts to 60 people. Sampling technique used sampling saturated. Collecting data using questionnaires designed using level Likert scale 1-5. Data analysis using SPSS structural model.The test results prove 1). Character (X1) partially significant effect on the smoothness of Payments (Y) Installment of Customer in Bank BRI unit Gumilir Cilacap with great influence 25.3%. 2). Capacity (X2) significant effect partially to the smoothness of Payments (Y) Installment of Customer in Bank Rakyat Indonesia Unit Gumilir Cilacap employee performance with great influence 26.7%. 3). Capital (X3) but not significant effect partially on Smoothness Payments (Y) Installment of Customer in Bank BRI Unit Gumilir Cilacap (1.1%). 4). Collateral (X4) significant effect partially to the smoothness of Payments (Y) Installment of Customer in Bank BRI Unit Gumilir against the influence of 27.5%. 5). Condition of Economy (X5) but not significant effect partially on Smoothness Payments (Y) Installment of Customer in Bank BRI Unit Gumilir Cilacap (0.7%). 6). Prerequisites Credit (5C) but not significant effect simultaneously on the smoothness of Payments (Y) Installment of Customer in Bank BRI Unit Gumulir Cilacap.Keywords:Character, Capital, Collateral, Capacity, Conditions of economy